english: english - Roy Jodi Martin Pohan; Dewi Iryani; Puguh Aji Haris Setiawan (CV. AFDIFAL MAJU BERKAH, 2026)
The use of third-party collateral in loan agreements is a common practice in Indonesia, yet it becomes legally complex when the principal debtor is declared bankrupt. This research examines the legal status of third-party collateral and the scope of the curator's authority in bankruptcy proceedings under Articles 55–60 of Law No. 37 of 2004, focusing on the interpretation of the phrase